Towards Competitive Advantage: Employee Competency Development Strategies in Promoting Business Innovation - Sutrisno, Sutrisno; Ausat, Abu Muna Almaududi; Suherlan, Suherlan; Rijal, Syamsu (CV Firmos, 2024)
The current business era is marked by increasingly fierce competition across various industry sectors. Innovation stands as a key element in creating competitive advantage. This research aims to investigate the relationship between employee competency development and business innovation, as well as to identify best practices in employee competency development leading to the creation of competitive advantage. The research method employed is a literature review with a qualitative approach and descriptive analysis. Google Scholar will be the primary source for data collection, spanning from 2012 to 2023. The study findings indicate that in the era of globalization and escalating competition, competitive advantage becomes paramount for business success. Employee competency development is a crucial element in achieving this advantage. It involves enhancing employees' knowledge, skills, and attitudes through various methods, including training, mentoring, and self-directed learning. The importance of employee competency development lies in the ability to create a workplace environment supportive of continuous learning and growth. This enables companies to have competent, adaptive, and innovative teams capable of effectively addressing market and technological changes.